Building academic language. : essential practices for content classrooms, grades 5-12. - Zwiers, Jeff. (San Francisco: Jossey Bass, 2008)
Building Academic Language shows what teachers can do to help all students develop the language needed to reach high levels of academic achievement." "Developing academic language involves more than acquiring content-specific vocabulary; it includes learning a wide range of general utility words, figurative expressions, grammatical conventions, and discussion strategies. Drawing from current theory and research, this book provides insights and practical guidance." "Building Academic Language offers many practical activities and classroom examples as well as a wide range of tips, tools, templates, and rubrics to help teachers integrate language development into content instruction and assessment every busy day."--Jacket.
Includes bibliographical references (p. 277-288) and index.
Keywords: Academic language -- Study and teaching